Improving the English language curriculum at the university level using a human rights approach - Meric, Olivier Gerard Angel (2012)
The curriculum model developed for English language instruction at the Universidad Estatal Amazonica is based on a human rights approach. This curriculum model aims to set contents and strategies so that the learners will develop the linguistic competences that satisfy their needs and objectives, and is an adaptation of the curriculum methods developed by the language educator Jack C. Richards. The success of the curriculum method was analyzed taking into account three criteria: the acquired level, the linguistic competences reached and the didactic resources used in order to evaluate its impacts on the learning process. The research was conducted with the entire learner population of the UEA during a semester using a descriptive statistic to analyze the results. The difference between the two semesters in terms of the number of student who had completed their level is of 17,6% which confirms an improvement of the learning process, but the results of the linguistic competence criterion did not fulfill the expectations at an acceptable rate. An investigation that examines more deeply the issues involved is necessary to determine if the English curriculum model based on a human rights approach will facilitate the development of the UEA students’ linguistic competences which are necessary for language proficiency.